Penerapan Etika Bisnis Islam dan Prinsip Budaya Bugis Sebagai Strategi Penguatan Karyawan pada CV Surya Indah Group - Ayu Puspa Kirana; Aksi Hamzah; Sitti Nikmah Marzuki (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the implementation of Islamic business ethics and Bugis cultural principles as a strategy for employee empowerment at CV Surya Indah Group in Bone Regency. In today’s highly competitive business environment, empowering employees is a key factor in achieving organizational success, especially when approached through local cultural and spiritual values. This research employs a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews, direct observation, and documentation involving both employees and management. The findings reveal that Islamic business ethics values such as siddiq (honesty), amanah (trustworthiness), tabligh (communicativeness), and fathanah (wisdom) have been internalized in the company’s work culture. Furthermore, Bugis cultural values such as sipakatau (mutual respect), sipakalebbi (mutual honor), and getteng (firmness in principle) strengthen employee loyalty and responsibility toward the organization. The synergy between these religious and cultural values has proven effective in fostering a harmonious work environment, enhancing motivation, and encouraging long-term employee retention. The implication of this study suggests that organizations can sustainably strengthen human resources by integrating local cultural wisdom and Islamic ethics into their employee management strategies.